Antioxidant effect induced by the essential oil of Pituranthos scoparius in a formulation of a whey spread emulsion. Issue 5 (9th January 2017) - Chikhoune, Anis; Damjan Pavleca, Jan; Shashkov, Mikhail; Berroua, Zahra; Chebbi, Kaissa; Bougherra, Hind; Zeroual, Brahim; Aliane, Khellaf; Gagaoua, Mohammed; Boudjellal, Abdelghani; Vovk, Irena; Križman, Mitja
Abstract: This study falls within the framework of industrial exploitation of the essential oil recovered from Pituranthos scoparius . Chromatographic techniques, namely TLC, HPTLC, MHE‐GC‐FID‐MS, GC X GC, and GC‐FID‐MS have been used for the characterization, identification and quantification of 48 compounds, divided into three major terpene groups: monoterpenes, diterpenes, and oxygenated compounds. The essential oil displayed an antioxidant activity, presented by a radical scavenging activity and evaluated by the TLC–DPPH method. Tests conducted at laboratory scale showed high protection from lipid oxidation of the spread emulsion, with an oxidative stability of 20.82 h. A sensory evaluation was carried out on emulsions incorporated with the essential oil. The PCA analysis revealed the effect of some attributes on the segregation between the four emulsions formulated. These data suggest that the essential oil of Pituranthos scoparius is a possible and promising candidate as a biopreservative at an industrial scale for food preservation. Practical applications: Essential oil of Pituranthos scoparius is traditionally used in folk medicine as a remedy for several illnesses. Its antibacterial properties are also exploited in the preservation of traditional cheese making. Whey is a by‐product of cheese and casein industries, still considered as a waste. Valorization of this by‐product in a whey spread emulsion is considered in the present work. Due to the bioactive compounds contained in the essential oil (such as terpinen‐4‐ol), the essential oil exhibits high antioxidant activity. As oxidation phenomena becomes a topical issue in fat and oil food industry, natural plants containing essential oils with high antioxidant properties are considered as good alternatives to synthetic antioxidants.